Developing Physics Monopoly Game Learning Media for Light and Optical Devices - Sari, Aprilia Mayang; Gunawan, Indra (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
This study aims to determine the specific needs, feasibility, and responses of teachers and students toward the developed physics learning media of monopoly game on the light and optical devices material. The research procedure was based on the 4-D model. The subjects of this study were the students of State Junior High School 2 Gadingrejo. Data was collected through questionnaire. The data collected were analyzed using descriptive statistics. The results of this study were; 1) to know the specific needs in the form of filters by researchers to eliminate, replace, or modify the various components of the game into educational elements and the need for materials such as paper art paper and linen suitable for printing monopoly game designs; 2) to know the media feasibility through media and material expert’s judgement. The average scores gained through the expert judgment were 4.45 and 4.24 respectively that fall into a very high category; 3) Teacher and student responses fall into the very high category with the mean score of 4.24 from teachers, 4.53 from small group testing and 4.59 from field-testing